Extreme Accusations and the Risk of Overaccusing - Bergstra, Jan Aldert; Düwell, Marcus (Transmathematica, 2024)
Proceeding on our initial work on types of accusation, we continue with an investigation of the fine structure of the class of straight accusations, with focus on what we will call “extreme accusations.” Besides “extreme accusation” we find the need for additional terminology such as “under accusing” and “over accusing.” Accusing comes with risks, which we investigate in some detail. Extreme accusation may arise from the intent to avoid a risk of under accusation, but it comes with a risk of over accusation, the gravity of which latter may be underestimated with unfortunate consequences.